HUBUNGAN MAKROSOMIA DENGAN KEJADIAN OBESITAS PADA ANAK YANG LAHIR DI RSUD MARGONO SOEKARDJO PURWOKERTO PERIODE JANUARI â DESEMBER 2010 - Sofia, Firda; Santosa, Qodri; Wicaksono, Madya Ardi (MANDALA of Health, 2014)
Background : Obesity is one of nutritional problems which often encountered, and potentially cause health disturbance due to several complications and high risk of comorbidity. Thare are several factors that may contribute as etiology and risk factors of obesity, like macrosomia.Purpose : To investigate the association between macrosomia and obesity in children who were born at Margono Soekardjo hospital Purwokerto from January to December 2010.Method : A cohort retrospective was conducted since October 2013 to April 2014. The subjects are babies with macrosomia (â¥4000g) and normal weight (2500-3999g) who were born at Margono Soekardjo hospital Purwokerto from January to December 2010 and resided in Banyumas. Total sampling was conducted. Birth weight of the subjects were seen in medical record. Body mass index was calculated and classified as obesity and normal using CDC curve by sex and age (â¥ 95th percentile). Data were analyzed using Chi-square and logistic regression.Results : Total sampels were 82 respondents composed of 44 boys and 38 girls, and found nineteen respondents were obese. Macrosomia associated with obesity, with p-value=0,018 and RR=2,80 (95%CI; 1,11â7,06) by chi-square test. Macrosomia, formula feeding and timing of introduction of complementary food effect to obesity, with p value < 0,05 using logistic regression.Conclusions : Macrosomic newborns were significantly associated with obesity in children who were born at Margono Soekardjo hospital Purwokerto from January to December 2010.